Eeman ka safar - Muhayyuddin Nawab (Ferozesons; Lahore, 2000)
"Eeman Ka Safar" by Muhayyuddin Nawab is a spiritual journey that follows the protagonist's quest for inner peace and faith, navigating the challenges of life while seeking divine guidance and truth.